On the Cauchy theorem for hyperholomorphic functions of spatial variable - Herus, O.F. (Український математичний вісник, 2017)
We proved a theorem about the integral of quaternionic-differentiable functions of spatial variable over the closed surface. It is an analog of the Cauchy theorem from complex analysis.